Wetland Utilization and Adaptation Practice of a Coastal Megacity: A Case Study of Chongming Island, Shanghai, China - Bao, Junlin; Gao, Shu (Frontiers in Environmental Science, 2021)
Coastal urban areas are faced with risks induced by global warming and sea level rise, which puts pressure on regional sustainable development. In particular, land use adjustment is closely related to climate change for a coastal megacity. Coastal wetlands on the edge of the megacity represent a vulnerable ecosystem and a key area in term of the resilient adaptation strategy. However, the interrelationship between the development of these wetlands and the megacity’s adaptation practice has not been sufficiently analyzed. From a historical perspective, based on document synthesis and field investigation, we attempt in this study to reveal long-term land use stages and driving factors in association with urban marginal wetlands, with a special reference to eastern Chongming Island, Shanghai. On such a basis, the future adaptation strategy of the megacity is evaluated. The analytical results show that this island has witnessed three periods of time for wetland utilization: traditional land use for salt production, fishery and agriculture before 1950, industrialization with rapid reclamation during 1950-2001, and the land use pattern orientated towards wetland ecosystem protection after 2002. The driving forces include sediment budget on the coast, wetland morphodynamic processes, sea level rise, population growth and resource management policy changes. Transformation occurred between the wetland utilization stages in response to the changes of these forcings. Furthermore, facing future climate change, there are different options of adaptation, e.g. retreatment and adherence ones. It may not be suitable for coastal cities with a large population to take the first option. It will be suitable for coastal communities to adhere to the location, if solutions to the problems of flooding risk, coastal erosion, and the maintenance of coastal facilities can be found. For eastern Chongming wetlands, as a key experimental area for ecosystem-oriented development in Shanghai, the transformation from the reclamation-oriented utilization towards the protection of wetland ecosystem represents the first step toward the latter option. We suggest that the next steps would be to maintain the ecological niche of the wetlands, to create new approaches to coastal engineering with contributions from the ecosystem, and to provide better ecosystem services.